Utilização da frutalina, uma lectina a d-galactose ligante de artocarpus incisa l., no estudo dos linfomas de hodgkin forma clássica - Constâncio, Ana Paula Nunes (2005)
Introduction: Neoplasic transformation is associated with alterations in the composition of cellular carbohydrates, which determine special cellular characteristics, such as behavior, growth, differentiation and adhesivity. Lectins are proteins which have affinity with specific carbohydrates, so they serve as tools in several fields of diagnostic and prognostic investigations on cancer and on metastases. Hodgkin’s Lymphoma (HL) is an heterogenous neoplasia in clinical, biological, and responsive aspects concerning treatment. There is currently an intense search for new markers which can have practical value in predicting HL behavior and prognosis. This study investigates, in cases of HL classical form (CHL) the expression of specific glyconjugates for Artocarpus incisa L (frutalin), a vegetable aD-galactose-binding lectin, in Reed-Sternberg cells (RS) and their variations. Materials and Methods: The study assessed 54 paraffin blocks containing lymphonodes with morphological and immunohistochemical diagnosis for CHL; 31 of the Nodular Esclerosis type (HLNE); 18 of the Mixed Cellularity type (HLMC); 3 of the Inter-folicular type (HLIN); and 2 of the Lymphocyte-rich type (HLLR). Then 3-mm histological cuts were made and fixed to sylated slides and processed through the strep-avidin-biotin-peroxidase technique (strep ABC), using the biotilinated frutalin (Fb) as probe. Cases of thyroid’s papillary carcinoma were considered positive controls; study’s cutoffs excluding Bf were considered negative ones. Clinical data were obtained through records review. Results: Three positivity patterns have been detected: cytoplasmic (Fbc), membranous (Fbm) and golgian (Fbg) (paranuclear punctiform coloration), which were also classified according to intensity: weak (+) and strong (++/+++). Global positivity for Fb in RS cells was 85.2% (46/54), same frequency as global positivity of CD15 sample. The Fbg marking pattern was the most frequent one, present in 91.3% (42/46) of positive cases (p=0.008). No statistically significant association was observed between frutalin markers, and clinical and stadiament data; initial response to treatment; CHL histological and phenotype subtype. Conclusion: Fb can be used as marker for RS cells and their variations. This use, associated with the morphological study, can be an useful tool for CHL diagnosis. With this number of cases, no correlation between marking pattern and clinical presentation or oncobiological factors that could be considered a prognosis indicator for CHL has been observed so far.